2003
DOI: 10.1016/s0016-7037(03)00276-x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary mineralization pathways induced by dissimilatory iron reduction of ferrihydrite under advective flow

Abstract: Iron (hydr)oxides not only serve as potent sorbents and repositories for nutrients and contaminants but also provide a terminal electron acceptor for microbial respiration. The microbial reduction of Fe (hydr)oxides and the subsequent secondary solid-phase transformations will, therefore, have a profound influence on the biogeochemical cycling of Fe as well as associated metals. Here we elucidate the pathways and mechanisms of secondary mineralization during dissimilatory iron reduction by a common iron-reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
619
6
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 571 publications
(681 citation statements)
references
References 47 publications
49
619
6
1
Order By: Relevance
“…Iron extraction using 0.5 M HCl facilitates detection of adsorbed iron(II) or siderite precipitates, for example in rice field soil (Ratering and Schnell, 2000), but not magnetite (Fe 3 O 4 ) (Raiswell et al, 1994), which could have potentially been formed in goethite amended slurries. Magnetite is a mixed Fe(II)-Fe(III) mineral, which may be observed in closed systems upon secondary mineral transformations of iron(III) phases, especially ferrihydrite (Hansel et al, 2003). Slightly higher levels of inorganic carbon (calculated from headspace CO 2 and Stable isotope probing of iron-reducing microorganisms T Hori et al slurry pH) were formed in goethite (2.9 mmol) compared with control treatments (2.2 mmol) and more acetate was degraded in goethite (65%) than in control treatments (44%).…”
Section: Stable Isotope Probing Of Iron-reducing Microorganisms T Hormentioning
confidence: 99%
“…Iron extraction using 0.5 M HCl facilitates detection of adsorbed iron(II) or siderite precipitates, for example in rice field soil (Ratering and Schnell, 2000), but not magnetite (Fe 3 O 4 ) (Raiswell et al, 1994), which could have potentially been formed in goethite amended slurries. Magnetite is a mixed Fe(II)-Fe(III) mineral, which may be observed in closed systems upon secondary mineral transformations of iron(III) phases, especially ferrihydrite (Hansel et al, 2003). Slightly higher levels of inorganic carbon (calculated from headspace CO 2 and Stable isotope probing of iron-reducing microorganisms T Hori et al slurry pH) were formed in goethite (2.9 mmol) compared with control treatments (2.2 mmol) and more acetate was degraded in goethite (65%) than in control treatments (44%).…”
Section: Stable Isotope Probing Of Iron-reducing Microorganisms T Hormentioning
confidence: 99%
“…The solid Fe speciation was determined by linear combination fitting of Fe EXAFS data as used previously [30] and described in more detail in the Supporting Information. Uranium EXAFS scans were processed using the computer programs Athena [6,31,32], SixPACK [33], and Feff7 [34] (Supporting Information).…”
Section: Solid Phase Analysismentioning
confidence: 99%
“…Ferrihydrite was prepared according to the method described by Brooks et al (32), and then coated quartz sand as reported previously (32,33). Iron concentration on the sand was approximately 10 g Kg -1 (1% by weight).…”
Section: Uranium(vi) Incorporation Experimentsmentioning
confidence: 99%